Bio- and chemo- mechanical processes in geotechnical engineering : Geotechnique Symposium in Print 2013 - Laloui, Lyesse (ICE Publishing, 2014)
The seventeenth Geotechnique Symposium in Print took place at the Institution of Civil Engineers on 3 June 2013 and sought to address the new challenges that are emerging from the interactions between multi-physical phenomena. These proceedings bring together the international research presented at the symposium and published across two issues Geotechnique and as well as additional subsequent research published in the journal. The papers selected for the symposium cover a wide range of geotechnical processes including: experimental analysis and constitutive modelling of the bio- and chemo-mechanical behaviour of geomaterials, effects of changes in the pore water chemistry on soil and rock behaviour, and interactions between geometrical scales of diverse biological, chemical, physical and mechanical processes.